Subject Cataloguing in COBISS System - Grbić, Branislava (Infotheca - Journal for Digital Humanities, 2024)
Obligatory elements of subject cataloguing in the COBISS system are subject heading and UDC classification. The rules established by the National Library of Serbia, based on international standards, are used for the determination of subject headings and subheadings. Indexing depth depends on the needs of library users.